Sonodynamic effect based on vancomycin-loaded microbubbles or meropenem-loaded microbubbles enhances elimination of different biofilms and bactericidal efficacy - Liqin Yao; Chenghan Chu; Yicheng Li; Li Cao; Jianhua Yang; Wenbo Mu (Bone & Joint Research, 2024)
Aims: This study investigated vancomycin-microbubbles (Vm-MBs) and meropenem (Mp)-MBs with ultrasound-targeted microbubble destruction (UTMD) to disrupt biofilms and improve bactericidal efficiency, providing a new and promising strategy for the treatment of device-related infections (DRIs). Methods: A film hydration method was used to prepare Vm-MBs and Mp-MBs and examine their characterization. Biofilms of methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli were treated with different groups. Biofilm biomass differences were determined by staining. Thickness and bacterial viability were observed with confocal laser scanning microscope (CLSM). Colony counts were determined by plate-counting. Scanning electron microscopy (SEM) observed bacterial morphology. Results: The Vm-MBs and Mp-MBs met the experimental requirements. The biofilm biomass in the Vm, Vm-MBs, UTMD, and Vm-MBs + UTMD groups was significantly lower than in the control group. MRSA and E. coli biofilms were most notably damaged in the Vm-MBs + UTMD group and Mp-MBs + UTMD group, respectively, with mean 21.55% (SD 0.08) and 19.73% (SD 1.25) remaining in the biofilm biomass. Vm-MBs + UTMD significantly reduced biofilm thickness and bacterial viability (p = 0.005 and p < 0.0001, respectively). Mp-MBs + UTMD could significantly decrease biofilm thickness and bacterial viability (allp < 0.001). Plate-counting method showed that the numbers of MRSA and E. coli bacterial colonies were significantly lower in the Vm-MBs + UTMD group and the Mp, Mp-MBs, UTMD, Mp-MBs + UTMD groups compared to the control group (p = 0.031). SEM showed that the morphology and structure of MRSA and E. coli were significantly damaged in the Vm-MBs + UTMD and Mp-MBs + UTMD groups. Conclusion: Vm-MBs or Mp-MBs combined with UTMD can effectively disrupt biofilms and protectively release antibiotics under ultrasound mediation, significantly reducing bacterial viability and improving the bactericidal effect of antibiotics. Cite this article: Bone Joint Res 2024;13(9):1–11.